PENGARUH SANKSI PAJAK DAN KEADILAN PAJAK TERHADAP PERSEPSI MAHASISWA AKUNTANSI MENGENAI PENGGELAPAN PAJAK - Purnayasa, I Kadek Wage (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.04.TAHUN.2022, 2022)
When tax sanctions are deemed burdensome, it will encourage taxpayers to commit tax evasion. If the prevailing justice is not in accordance with the norm, the taxpayer will legitimize the action to commit tax evasion. This study aims to determine the effect of tax sanctions and tax fairness on student perceptions of tax evasion. This research was conducted in Accounting students of the FEB, Udayana University in the class of 2017. The population in this study were Accounting students of the Faculty of Economics and Business of Udayana University in the class of 2017. The sample used is 100 samples. The analytical technique used in this research is multiple linear regression analysis. The test results in this study found that tax sanctions have a positive and significant effect on tax evasion and tax justice has a positive and significant effect on tax evasion. This shows that the higher the tax sanctions and tax equity, the higher the accounting student's perception of tax evasion.